Pengaruh Penerimaan Pajak Daerah Terhadap Pendapatan Asli Daerah (Pad) Kabupaten Boyolali Tahun 2017-2020 - Afaf Nur Maesyaroh; Hadi Samanto; M. Hasan Ma’ruf (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2022)
The purpose of this study is to determine the effect of local tax revenues on local original income in the government in Boyolali Regency for the 2017-2020 period. This research is quantitative using secondary data, with the population and samples being the PAD Budget Realization Report and the regional tax revenue report for 2017-2020. Based on the results of the t test, it is known that the PBB-P2 and the Entertainment Tax have a significant effect on local original income, while groundwater tax has no effect on local original income. Based on Test F shows that jointly PBB-P2, Groundwater Tax, Entertainment Tax has a significant effect on Local Native Income.